Redesign Struktur Gedung Madrasah Aliyah Madrasatul Qur’an Tebuireng Jombang Dengan Penggunaan Beton Pracetak - Mohammad Johan; Titin Sundari; Meriana Wahyu Nugroho; Rahma Ramadhani (Jurnal Sipil Terapan, 2023)
Precast concrete is a concrete structure construction technology with more printed components in the factory. Here the researcher takes into account to determine the planning of structural elements using precast concrete and its connections. The Madrasatul Qur'an MA Building in Nanggungan Village was used as the object of research to take into account floor plates, beams and columns, with reference to SNI 2847 – 2019, aspects of repetition, connections on beams, columns (Crobel) and floor plates. The calculation results on a 20 cm thick plate + overtoping with repeating plates of dimensions of 15 cm and 5 cm, overtoping using pedestal reinforcement D8 – 135 mm in the X direction, using wermesh D8 – 135 mm on the pedestal in the Y direction. planned 2 models of beam dimensions of 40 cm x 60 cm, upper reinforcement 5 D16 pedestal, 4 D16 field, lower reinforcement 4 D16 pedestal, 5 D16 pitch, Ø 10 – 150 fulcrum, Ø 10 – 150 pitch, waist reinforcement 2 D13 fulcrum, 2 D13. Beam model 2 upper reinforcement 3 D16 pedestal, 3 D16 pitch, rebar Ø 10 – 150 fulcrum, Ø 10 – 150 pitch, waist reinforcement 2 Ø 13 fulcrum, 2 Ø 13 pitch. The connection between the beam and the plate relies on a pedestal mounted lengthwise, the connection of the column beam uses a short console.